Evaluation of health insurance policy impact on maternal and child health outcomes in coastal areas - Saman Saman (JAKESPOL Journal of Health Policy Analysis, 2026)
Introduction: Maternal and child healthcare inequities remain a major challenge in coastal communities despite the implementation of national health insurance programs. This study aimed to evaluate the impact of health insurance policy implementation on maternal and child health outcomes in coastal areas. Methods: A quantitative cross-sectional analytical study was conducted in several coastal districts in Eastern Indonesia between January and April 2026. A total of 348 mothers with children under five years old were selected using multistage cluster sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics, chi-square tests, and multivariate logistic regression with a significance level of α = 0.05. Results: Active health insurance participation was significantly associated with improved maternal and child healthcare access. Multivariate analysis showed that distance to healthcare facilities was the strongest predictor of limited healthcare access (AOR = 3.46; 95% CI: 2.01–5.95; p < 0.001). Non-insured respondents were more likely to experience healthcare access barriers (AOR = 2.84; 95% CI: 1.63–4.95; p < 0.001). Transportation limitations (AOR = 2.17; 95% CI: 1.28–3.69; p = 0.004) and low household income (AOR = 1.88; 95% CI: 1.09–3.23; p = 0.021) also significantly influenced healthcare accessibility. Conclusion: Health insurance policies improved healthcare utilization; however, structural barriers continued to limit equitable maternal and child healthcare access in coastal communities. Strengthening geographically responsive healthcare systems is necessary to optimize universal health coverage implementation.